The role of resveratrol as a natural modulator in glia activation in experimental models of stroke - Farzaneh Vafaee; Hamed Ghazavi; Shima Shirzad; fatemeh forouzanfar; Sajjad SahabNegah; Mona Riyahi Rad (Mashhad University of Medical Sciences, 2020)
Objective: Stroke is one of the most important causes of death and disability in modern and developing societies. In a stroke, both the glial cells and neurons develop apoptosis due to decreased cellular access to glucose and oxygen. Resveratrol (3, 5, 4'-trihydroxy-trans-stilbene) as a herbal compound shows neuroprotective and glioprotective effects. This article reviews how resveratrol can alleviate symptoms after stroke to help neurons to survive by modulating some signaling pathways in glia. Materials and Methods: Various databases such as ISI Web of Knowledge, Scopus, Medline, PubMed, and Google Scholar, were searched from 2000 to February 2020 to gather the required articles using appropriate keywords. Results: Resveratrol enhances anti-inflammatory and decreases inflammatory cytokines by affecting the signaling pathways in microglia such as AMP-activated protein kinase (5' adenosine monophosphate-activated protein kinase, AMPK), SIRT1 (sirtuin 1) and SOCS1 (suppressor of cytokine signaling 1). Furthermore, through miR-155 overexpressing in microglia, resveratrol promotes M2 phenotype polarization. Resveratrol also increases AMPK and inhibits GSK-3β (glycogen synthase kinase 3 beta) activity in astrocytes, which release energy, makes ATP available to neurons and reduces reactive oxygen species (ROS). Besides, resveratrol increases oligodendrocyte survival, which can lead to maintaining post-stroke brain homeostasis. Conclusion: These results suggest that resveratrol can be considered a novel therapeutic agent for the reduction of stroke symptoms that can not only affect neuronal function but also play an important role in reducing neurotoxicity by altering glial activity and signaling.